GAYA BAHASA DAN PESAN MORAL DALAM PUISI TERPILIH WILLIAM SHAKESPEARE - Galuh Anggraini; Soenarjati Djajanegara (INFERENCE: Journal of English Language Teaching, 2020)
The aim of the research is to find out the use of figurative languages, thedominant one, and the moral values in the selected poems of William Shakespeare. Thisresearch uses a qualitative descriptive method. The results obtained include: there are 14 kinds of figurative language used in the selected poems, they are metaphor, simile, symbol, personification, litotes, hyperbole, metonymy, synecdoche, allusion, alliteration,repetition, assonance, parallelism, and paradox. The dominant of figurative language used in the selected poems is a metaphor. There are five moral values, such as appreciation, joy, love, honesty, and loyalty.Keywords: literature; figurative language; moral value; poetry